Prototype Filterisasi Udara Otomatis Pada Masker Berbasis Arduino - Muhammad Fauzan Akbar; Ade Zulkarnain Hasibuan; Adidtya Perdana (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
The world was shocked by the outbreak of a new virus that originated in the city of Wuhan, Hubei province in China and has spread to all corners of the world. This virus is Corona Virus Disease 2019 (Covid-19). The government as a policy maker has imposed new regulations so that everyone can leave the house and do work without having to worry about being exposed to the Covid-19 virus. One of the regulations made by the government is that everyone who will leave the house must wear a mask. However, the use of masks for a long time has the potential to cause headaches to increase respiratory tract resistance caused by carbon dioxide. It is necessary to have a mask that can filter the air properly so that carbon dioxide can come out of the mask directly and not be inhaled again. To overcome this problem, it is necessary to make a tool that can make air or carbon dioxide out of the mask. With existing technological facilities, the problem of breathing in carbon dioxide in masks can be minimized. One example is the MG811 sensor technology where this technology can detect the presence of carbon dioxide in the mask that comes out of human breathing. Based on this, this study discusses the automatic air filter system on an Arduino-based mask. The result of testing and implementing this system is that when the sensor detects excess carbon dioxide in the mask, then the supporting component of the system, namely the fan, will work to remove carbon dioxide in the mask.